Shifts in excitatory/inhibitory balance by juvenile stress: A role for neuron–astrocyte interaction in the dentate gyrus. Issue 6 (15th February 2016) - Albrecht, Anne; Ivens, Sebastian; Papageorgiou, Ismini E.; Çalışkan, Gürsel; Saiepour, Nasrin; Brück, Wolfgang; Richter‐Levin, Gal; Heinemann, Uwe; Stork, Oliver
Abstract : Childhood trauma is a well‐described risk factor for the development of stress‐related psychopathology such as posttraumatic stress disorder or depression later in life. Childhood adversity can be modeled in rodents by juvenile stress (JS) protocols, resulting in impaired coping with stressful challenges in adulthood. In the current study, we investigated the long‐lasting impact of JS on the expression of molecular factors for glutamate and γ‐aminobutyric acid (GABA) uptake and turnover in sublayers of the dentate gyrus (DG) using laser microdissection and quantitative real‐time polymerase chain reaction. We observed reduced mRNA expression levels after JS for factors mediating astrocytic glutamate and GABA uptake and degradation. These alterations were prominently observed in the dorsal but not ventral DG granule cell layer, indicating a lasting change in astrocytic GABA and glutamate metabolism that may affect dorsal DG network activity. Indeed, we observed increased inhibition and a lack of facilitation in response to paired‐pulse stimulation at short interstimulus intervals in the dorsal DG after JS, while no alterations were evident in basal synaptic transmission or forms of long‐term plasticity. The shift in paired‐pulse response was mimicked by pharmacologically blocking the astrocytic GABA transporter GAT‐3 in naïve animals. Accordingly, reduced expression levels of GAT‐3 were confirmed at the protein level in the dorsal granule cell layer of rats stressed in juvenility. Together, these data demonstrate a lasting shift in the excitatory/inhibitory balance of dorsal DG network activity by JS that appears to be mediated by decreased GABA uptake into astrocytes. GLIA 2016;64:911–922 Main points: Juvenile stress reduced DG expression of GLT‐1, GAT‐3. Juvenile stress enhanced DG paired pulse inhibition, mimicked by GAT‐3 blockage. Astrocytic GABA uptake contributes to lasting shifts of DG excitatory/inhibitory balance after juvenile stress.